Limousin cattle production performance and farmer income post-FMD fed with super booster and immunobooster concentrate - Maghfiroh, Nurutin Tutur Bifatikhatil M; Al Arif, Mohammad Anam; Lamid, Mirni; Mustofa, Imam; Mufasirin, Mufasirin; Rahardjo, Dadik (Politeknik Negeri Jember, 2025)
This study aims to evaluate the administration of super booster, and immunobooster concentrates on production performance and farmers' income following an outbreak of foot and mouth disease (FMD) by proving the improvements in production performance, including feed consumption, weight gain, and revenue of crossbred Limousin cattle farmers. This study used 18 male Limousin crossbred cattle selected based on age (1.5-2 years) and having been infected with FMD virus that is divided into three treatments: T0 (control feed consisting of forage and local concentrate), T1 (control feed + 40 g of a super booster), and T2 (control feed + 600 g of immunobooster concentrate). Data collection and observation were conducted over 42 days. Statistical analysis was performed using analysis of variance (ANOVA) based on the completely randomized design (CRD), followed by Duncan’s multiple range test (DMRT). The results of the variance analysis showed a p-value of <0.05, indicating that the addition of super booster and immunobooster can improve feed consumption, body weight gain, and increase farmers income in crossbred Limousin cattle farming following an outbreak of FMD, so that it can be used as an alternative step in overcoming post-FMD losses and helping farmers maximize profits.